How our food choices affect the climate - Wollenberg, Eva Karoline (2022)
"How food choices affect the climate" was presented by Lini Wollenberg, given for the Frontiers Sustainability Speaker Series on January 13, 2022. She summarizes various food systems' emissions contributions and discusses the scaling up of plant-based meat. Additional attached resources include the CCAFS AgLED website, the ACE Calculator, Our World in Data, and FAO emission intensity and food systems data.